Observation of ? (3686) ?e+e-?cJ and ?cJ ?e+e-J /? - Çetin, Serkant Ali (Amer. Physical Soc., 2017)
Using 4.479×108???(3686) events collected with the BESIII detector, we search for the decays ?(3686)?e+e??cJ and ?cJ?e+e?J/?, where J=0, 1, 2. The decays ?(3686)?e+e??cJ and ?cJ?e+e?J/? are observed for the first time. The measured branching fractions are B(?(3686)?e+e??cJ)=(11.7±2.5±1.0)×10?4, (8.6±0.3±0.6)×10?4, (6.9±0.5±0.6)×10?4 for J=0, 1, 2, and B(?cJ?e+e?J/?)=(1.51±0.30±0.13)×10?4, (3.73±0.09±0.25)×10?3, (2.48±0.08±0.16)×10?3 for J=0, 1, 2, respectively. The ratios of the branching fractions B(?(3686)?e+e??cJ)/B(?(3686)???cJ) and B(?cJ?e+e?J/?)/B(?cJ??J/?) are also reported. Also, the ? values of helicity angular distributions of the e+e? pair are determined for ?(3686)?e+e??c1,2 and ?c1,2?e+e?J/?.